Activation of the Regulatory T-Cell/Indoleamine 2,3-Dioxygenase Axis Reduces Vascular Inflammation and Atherosclerosis in Hyperlipidemic Mice - Forteza, Maria J.; Polyzos, Konstantinos A.; Baumgartner, Roland; Suur, Bianca E.; Mussbacher, Marion; Johansson, Daniel K.; Hermansson, Andreas; Hansson, Göran K.; Ketelhuth, Daniel F. J. (Frontiers in Immunology, 2018)
T-cell activation is characteristic during the development of atherosclerosis. While overall T-cell responses have been implicated in disease acceleration, regulatory T cells (Tregs) exhibit atheroprotective effects. The expression of the enzyme indoleamine 2,3-dioxygenase-1 (IDO), which catalyzes the degradation of tryptophan (Trp) along the kynurenine pathway, has been implicated in the induction and expansion of Treg populations. Hence, Tregs can reciprocally promote IDO expression in dendritic cells via reverse signaling mechanisms during antigen presentation. In this study, we hypothesize that triggering the ‘Treg/IDO axis’ in the artery wall is atheroprotective. We show that apolipoprotein B100-pulsed TGFβ2-treated tolerogenic dendritic cells promote de novo FoxP3+ Treg expansion in vivo. This local increase in Treg numbers is associated with increased vascular IDO expression and a robust reduction in the atherosclerotic burden. Using human primary cell cultures, we show for the first time that IDO expression and activity can be regulated by cytotoxic T-lymphocyte associated protein-4 (CTLA4), which is a constitutive molecule expressed and secreted by Tregs, in smooth muscle cells, endothelial cells, and macrophages. Altogether, our data suggest that Tregs and IDO-mediated Trp metabolism can mutually regulate one another in the vessel wall to promote vascular tolerance mechanisms that limit inflammation and atherosclerosis.